2011
DOI: 10.1111/j.1365-2362.2011.02478.x
|View full text |Cite
|
Sign up to set email alerts
|

Diet-induced dyslipidemia impairs reverse cholesterol transport in hamsters

Abstract: Overall, these data demonstrate that diet-induced dyslipidemia severely impairs in vivo RCT in hamsters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
25
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 29 publications
3
25
1
Order By: Relevance
“…A recent report showed that diet-induced dyslipidemia impaired macrophage-to-feces RCT in hamsters fed a low-fat diet containing 0.3% cholesterol, although it did cause a pronounced increase in HDL-C. 51 Hamsters express CETP, but the HFHC diet also promoted RCT in our CETP transgenic mice. The differences in these results may be attributable to the specific diet-induced changes in the liver gene expression profile of hamsters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent report showed that diet-induced dyslipidemia impaired macrophage-to-feces RCT in hamsters fed a low-fat diet containing 0.3% cholesterol, although it did cause a pronounced increase in HDL-C. 51 Hamsters express CETP, but the HFHC diet also promoted RCT in our CETP transgenic mice. The differences in these results may be attributable to the specific diet-induced changes in the liver gene expression profile of hamsters.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the observed increased macrophage-specific RCT is an insufficient, compensatory mechanism to protect against atherosclerosis development. Therefore, HFHC diet-mediated effects on HDL antiinflammatory activity, 49 non-HDL-C, and fat cells and macrophage inflammation 50 appear to be the major contributor to atherosclerosis in these mice.A recent report showed that diet-induced dyslipidemia impaired macrophage-to-feces RCT in hamsters fed a low-fat diet containing 0.3% cholesterol, although it did cause a pronounced increase in HDL-C. 51 Hamsters express CETP, but the HFHC diet also promoted RCT in our CETP transgenic mice. The differences in these results may be attributable to the specific diet-induced changes in the liver gene expression profile of hamsters.…”
mentioning
confidence: 99%
“…Meanwhile, an animal model that reflects the human situation (e.g., fat and fructose overconsumption) would be helpful to evaluate novel therapies targeting metabolic syndrome. We recently demonstrated the relevance of the hamster model for studying RCT (11)(12)(13), because this CETP-expressing species has a similar lipoprotein metabolism to humans (11). In the present study, Golden Syrian hamsters were fed a high fat/ fructose-enriched (HF) diet to induce the main features of human metabolic syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…Except steroidogenic tissues, cells in general, are unable to metabolize cholesterol, so the non-esterified cholesterol excess is carried by the liver, to the biliary and fecal output. However, this mechanism may become inefficient, and cholesterol accumulates in the hepatocytes [40]. Indeed, HFS and HFS-PO animals had higher hepatic cholesterol accumulation and higher fecal output.…”
Section: Discussionmentioning
confidence: 99%